Men and ‘Women’s Magic’: Contested Narratives of Gender, Seidhr, and ‘Ergi’ - Blain, Jenny; Wallis, Robert (Pomegranate, 1999)
Seidhr appears most often as a female activity... male seidh workers were spoken of as 'ergi', a term of insult relating to behaviour seen as 'unmanly'.